PENINGKATAN PEMAHAMAN PEREMPUAN TENTANG GIZI DAN KEAMANAN PANGAN SEBAGAI UPAYA AWAL PENCEGAHAN STUNTING - Pudjihartati, Endang; Herawati, Maria Marina; Prihtanti, Tinjung Mary; Novinanto, Antonius (Jurnal Abdi Insani, 2025)
The problem of stunting is still a global concern to be addressed by various parties. Overcoming stunting requires a multi-sectoral approach, including nutrition education and better access to nutritious food. Educating women about nutrition and food safety is the first step in preventing stunting. Kalibening urban village in Salatiga City has the highest number of stunting cases among other urban villages. This community service activity aims to educate the female community, especially members of the Kalibening Village PKK, about nutrition and food safety as an initial effort to prevent stunting. This community service activity applies the extension technique, which is a technique to increase the knowledge and insight of community service activity participants through original explanation tutorials. A total of 28 women who are members of the PKK RW III attended as counselling participants in community service activities. The materials presented in the counselling activities include the types of nutrients needed by the body, nutritional values in various types of food, introduction to the B2SA menu (Diverse, Nutritious, Balanced, and Safe), especially nutritious food for children and pregnant women, and how to store and process safe food. Evaluation of the response to the results of extension activities carried out through filling out questionnaires showed good results, including satisfaction with the material presented in the extension activities, satisfaction with the resource persons, satisfaction with the extension facilities or infrastructure used, satisfaction with the extension activities as a whole. The response of PKK members to extension activities is very good, with a mode of satisfaction score of 3.